A Genetic Study of Two Sex-linked Recessive Mutants, Marginal Cell Less (MCL) Wing Cut (CT) Wing of Drosophila ananassae - De Silva, B.G.D.N.K. (My University, 1989)
The present study was made in order to carry out further genetic investigations of two mutants ct wing and mcl wing isolated by Bogabawatta in 1982. These two mutants were observed to be recessive and sex-linked, but were also seen not to -strictly obey Mendelian rules. In the absence of the wild allele the mutants allele behaves in a peculiar manner. Each mutantallele is capable of producing all the types of mutants such as ct wing mcl wing, and ct-mcl wing along with the wild types. The most probable explanation for this peculiar behaviour is that these two allele are unstable.